DHW-208, A Novel Phosphatidylinositol 3-Kinase (PI3K) Inhibitor, Has Anti-Hepatocellular Carcinoma Activity Through Promoting Apoptosis and Inhibiting Angiogenesis - Wang, Shu; Wu, Yuting; Liu, Mingyue; Zhao, Qingchun; Jian, Lingyan (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common tumors worldwide with high prevalence and lethality. Due to insidious onset and lack of early symptoms, most HCC patients are diagnosed at advanced stages without adequate methods but systemic therapies. PI3K/AKT/mTOR signaling pathway plays a crucial role in the progression and development of HCC. Aberrant activation of PI3K/AKT/mTOR pathway is involved in diverse biological processes, including cell proliferation, apoptosis, migration, invasion and angiogenesis. Therefore, the development of PI3K-targeted inhibitors is of great significance for the treatment of HCC. DHW-208 is a novel 4-aminoquinazoline derivative pan-PI3K inhibitor. This study aimed to assess the therapeutic efficacy of DHW-208 in HCC and investigate its underlying mechanism. DHW-208 could inhibit the proliferation, migration, invasion and angiogenesis of HCC through the PI3K/AKT/mTOR signaling pathway in vitro. Consistent with the in vitro results, in vivo studies demonstrated that DHW-208 elicits an antitumor effect by inhibiting the PI3K/AKT/mTOR-signaling pathway with a high degree of safety in HCC. Therefore, DHW-208 is a candidate compound to be developed as a small molecule PI3K inhibitor for the treatment of HCC, and our study provides a certain theoretical basis for the treatment of HCC and the development of PI3K inhibitors.